The Berkeley Plato : from neglected relic to ancient treasure : an archaeological detective story - Miller, Stephen G. (Stephen Gaylord), 1942-2021 (Joan Palevsky imprint in classical literature., 2009)
This book explores the provenance of the so-called Berkeley Herm of Plato, a sculptural portrait that Stephen G. Miller first encountered over thirty years ago in a university storage basement. The head, languishing since its arrival in 1902, had become detached from the body, or herm, and had been labeled a fake. In 2002, while preparing another book, Miller-now an experienced archaeologist-needed an illustration of Plato, remembered this piece, and took another look. The marble, he recognized immediately, was from the Greek islands, the inscription appeared ancient, and the ribbons visible o.